EVALUATION OF THE IMPLEMENTATION OF THE REHABILITATION PROGRAM FOR DRUG ADDICTS IN BENGKULU CITY - Monika Dwi Yolanda; Bobby Mandala Putra; Hernowo Novi Yanto (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This research aims to evaluate the implementation of the drug addict rehabilitation program in Bengkulu City. This type of qualitative research uses a case study method or approach using observation, interview and documentation data collection techniques. The results of the research are the rehabilitation program at the BNN in the Bengkulu Province Rehabilitation Home. 1) While residents are undergoing rehabilitation with inpatient treatment at the BNN in the Bengkulu Province rehabilitation home, the residents take part in screening, assessment and counseling programs. 2) SOPs carry out program implementation, and SOPs are formed based on the applicable legal basis regarding drug abuse. 3) Carrying out assessment interviews using the 7 domains contained in the ASI form, namely, General, Medical, Economic, Drugs (Substances), Legal (Law), Family, and Psychiatry 3) Resident assessments using SMART (Specific, Measurable, Achievable , Relevant, Time-bound).